Liquidity, Activity, Solvency, Profitability on Company Value Mediated by Investment Decision - Budiarti, Sandy; Moeldjadi, Moeldjadi; Wijayanti, Risna (International Journal Labs, 2023)
A country with high economic potential in the international community is Indonesia. Indonesia is one of the countries with positive economic growth amidst the current global uncertainty. Indonesia's current economic growth is quite high in the region of other ASEAN countries. This study discussed liquidity, solvency, and profitability on company value with investment decisions as a mediating variable. This research used a quantitative approach with a descriptive quantitative design carried out at the Investment Gallery, Faculty of Economics and Business, Brawijaya University in 2018-2022. This study shows that investment decisions do not mediate the effect of liquidity, activity, and solvency on company value. However, investment decisions can mediate the effect of profitability on company value.